2001
DOI: 10.2337/diabetes.50.8.1778
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Short-Term Administration of a Sulfonylurea (Gliclazide) Increases Pulsatile Insulin Secretion in Type 2 Diabetes

Abstract: The high-frequency oscillatory pattern of insulin release is disturbed in type 2 diabetes. Although sulfonylurea drugs are widely used for the treatment of this disease, their effect on insulin release patterns is not well established. The aim of the present study was to assess the impact of acute treatment and 5 weeks of sulfonylurea (gliclazide) treatment on insulin secretory dynamics in type 2 diabetic patients. To this end, 10 patients with type 2 diabetes (age 53 ؎ 2 years, BMI 27.5 ؎ 1.1 kg/m 2 , fasting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 41 publications
2
10
0
1
Order By: Relevance
“…We found no change in baseline insulin release regularity as measured by ApEn. Previous studies of native GLP-1 and another insulin secretagogue, gliclazide, gave similar results, and it has been suggested that intervention in the early diabetic or prediabetic state is necessary to prevent the deterioration of baseline insulin release regularity (8,34). Deconvolution analysis of baseline insulin time series revealed no substantial changes in the distribution of basal versus pulsatile insulin release consistent with findings in previous studies in patients with type 2 diabetes (8,35).…”
Section: Discussionsupporting
confidence: 77%
“…We found no change in baseline insulin release regularity as measured by ApEn. Previous studies of native GLP-1 and another insulin secretagogue, gliclazide, gave similar results, and it has been suggested that intervention in the early diabetic or prediabetic state is necessary to prevent the deterioration of baseline insulin release regularity (8,34). Deconvolution analysis of baseline insulin time series revealed no substantial changes in the distribution of basal versus pulsatile insulin release consistent with findings in previous studies in patients with type 2 diabetes (8,35).…”
Section: Discussionsupporting
confidence: 77%
“…Matthews et al [54] observed that elevated glucose increases the mass but not the frequency of plasma insulin bursts, and this has been confirmed in numerous studies ([55][56][57]). The action of glucose mainly to increase insulin pulse amplitude has also been observed in isolated human islets, where small numbers of islets could be perifused while insulin was sampled in their effluent [39].…”
Section: Introductionmentioning
confidence: 86%
“…Sulfonylureas, for example, which increase insulin secretion by closing KATP channels in the beta cell plasma membrane, acutely increase the amplitude, but not the frequency, of insulin pulse bursts or the basal insulin levels when studied in dogs [131], or in humans with T2DM [56]. An example of the modulation resulting from tolbutamide infusion is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…E hatások valamennyi SU esetében alárendelt jelentő-ségűek és másodlagosak: minden valószínűség szerint a prandialis inzulinelválasztás első fázisának erősödésével és a pulzatilis inzulinszekréció helyreállásával vagy javulásával állnak összefüggésben [35].…”
Section: A Su-k Nem Receptoriális Tulajdonságaiunclassified